The mediating effect of parental warmth on the association of parent pressure and athlete perfectionism in adolescent soccer - Fleming, D, J. M.; Dorsch, T. E.; Dayley, J. C. (International Journal of Sport and Exercise Psychology, 2023)
Appropriately designed sport contexts have the potential to offer participants a range of positive developmental outcomes across domains. However, excessive pressure from parents and an emphasis on achievement outcomes may lead young athletes to develop maladaptive personality characteristics such as perfectionism, which may undermine the positive outcomes from participating in sport. While parenting styles have been broadly explored in relation to the development of perfectionism, individual parenting behaviours have not been examined as unique predictors. The present study was designed to test the potential mediating role of perceived parental warmth on the association of perceived parent pressure and athletes` perfectionism in the context of competitive club soccer. Data were drawn from a sample of 149 adolescents in the United States who were participating in competitive club soccer. Results demonstrated an acceptable model fit with paternal pressure positively predicting both perfectionistic concerns and strivings, and perceived paternal warmth mediating the relationship between paternal pressure and perfectionistic strivings (ß = -.18, p < .05) and concerns (ß = -.19, p < .05). Perceived maternal pressure had no relationship with athlete perfectionistic strivings (ß = -.03, p = .38) or concerns (ß = -.02, p = .46). These findings extend knowledge of the pressure-perfectionism association while also accounting for the mediating effect of perceived parental warmth. The present study highlights the relationship between perceived paternal pressure and warmth in relation to perfectionism in competitive club soccer. Findings have the potential to inform future research examining parenting styles in the context of adolescent sport.